Picture-perfect science lessons : using children's books to guide inquiry, grades 3-6 - Ansberry, Karen Rohrich, 1966-; Morgan, Emily R., (Emily Rachel), 1973- (Arlington, VA : NSTAPress, 2005)
Presents a collection of fifteen lesson plans for the third through sixth-grade science classroom that use children's books to help develop interest in science, and contains reproducible student pages and assessments.
Includes bibliographical references and index.
Science and Children (N.S.T.A.).
Professional
Keywords: Children's books; Science -- Study and teaching (Elementary); Children's literature; Science -- Study and teaching